Transcriptomic analysis of the anti-inflammatory effect of Cordyceps militaris extract on acute gouty arthritis - Jiao, Chunwei; Liang, Huijia; Liu, Li; Li, Shunxian; Chen, Jiaming; Xie, Yizhen (Frontiers in Pharmacology, 2022)
Background: Gouty arthritis (GA) is a common inflammatory disease that causes pain due to the deposition of monosodium urate (MSU) crystals into joints and surrounding tissues. Anti-inflammatory drugs have significant clinical anti-inflammatory and analgesic effects, but they have many side effects. Cordyceps militaris is an edible and medicinal fungus, and its extract (CME) has good anti-inflammatory and analgesic effects. This study aimed to investigate the anti-inflammatory effect of CME on GA and its underlying mechanism. Methods: The effect of CME on the expression of related inflammatory factors and histopathological changes in the MSU-induced acute inflammatory gout model in rats was studied by ELISA and HE, and its anti-inflammatory mechanism was analyzed by transcriptome combined with RT-PCR. Results: CME significantly improved gait scores and joint swelling in GA rats, and reduced MSU-induced inflammatory cell infiltration. CME inhibited MSU-induced inflammatory responses by reducing the levels of pro-inflammatory factors TNF-α, interleukin (IL)-1β, IL-6, and Caspase-1 and increasing the anti-inflammatory factor IL-10. Transcriptome analysis showed that CME significantly altered inflammation-related cytokine pathways, and identified four major genes involved in regulation of inflammation, CCL7, CSF2RB, LIF, and IL-1β. In addition, real-time quantitative PCR (RT-qPCR) was performed to verify these differential genes. Conclusion: CME significantly alleviated the inflammatory progression of GA and ameliorated the onset of GA. The underlying mechanism may be related to triggering the cytokine-cytokine receptor interaction signaling pathway to inhibit the activation of the inflammasome and regulate the immune system. And it regulates the inflammatory response induced by MSU crystals through the genes CCL7, CSF2RB, and IL-1β.